2004
DOI: 10.1093/rheumatology/keh281
|View full text |Cite
|
Sign up to set email alerts
|

VEGF gene polymorphisms and susceptibility to rheumatoid arthritis

Abstract: Our data suggest that the VEGF gene may play a role in the development of RA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
76
1
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 33 publications
11
76
1
7
Order By: Relevance
“…All adjuvant-injected animals had higher levels of circulating VEGF compared with controls, which was expected because increased vascularization is a marker of inflammation (Han et al, 2004). Treatment with E in combination with RLX resulted in the greatest increase in circulating VEGF, consistent with the reported activity of RLX increasing VEGF expression during wound healing (Unemori et al, 2000).…”
Section: Figsupporting
confidence: 61%
See 1 more Smart Citation
“…All adjuvant-injected animals had higher levels of circulating VEGF compared with controls, which was expected because increased vascularization is a marker of inflammation (Han et al, 2004). Treatment with E in combination with RLX resulted in the greatest increase in circulating VEGF, consistent with the reported activity of RLX increasing VEGF expression during wound healing (Unemori et al, 2000).…”
Section: Figsupporting
confidence: 61%
“…Cytokines play an important role in the inflammation cascade, and changes in these proteins can be monitored to determine how a given treatment is altering disease progression. Some of the important proinflammatory cytokines involved in RA are interleukin (IL)-1␤, tumor necrosis factor (TNF) ␣ (Feldmann et al, 1996), and vascular endothelial growth factor (VEGF), an angiogenic cytokine (Han et al, 2004). Anti-inflammatory cytokines such as IL-10 are also of interest in RA research (Bach, 1996).…”
mentioning
confidence: 99%
“…The gene is highly polymorphic, and several single nucleotide polymorphisms (SNPs) have been associated with altered gene expression and higher VEGF plasma levels (3-7). In addition, previous studies have revealed a correlation with cancer development and progression (8)(9)(10)(11), as well as with Behcet's disease, adult respiratory distress syndrome, rheumatoid arthritis and psoriatic arthritis (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 96%
“…Однонуклеотидный полиморфизм (ОНП) ФРСЭ в позициях -2578 и -1154, расположенных в преде-лах промоторного региона, влияет на синтез ФРСЭ-А стимулированными периферическими мононуклеарами [8]. Генотип ФРСЭ-А -634 СС связан с более высокой сы-вороточной концентрацией ФРСЭ у здоровых лиц и с по-вышенной продукцией ФРСЭ мононуклеарами, стиму-лированными липополисахаридами, по сравнению с CG-и GG-генотипами [9,10]. Аллель ФРСЭ +813 T связан со значительным снижением уровня ФРСЭ в плазме у здо-ровых мужчин.…”
unclassified
“…Сообщалось лишь об изменении частоты распределения ряда полиморфизмов этого гена среди пациентов монголоидного происхождения с РА, в частности среди корейцев [9]. Исходя из этого целью настоящего исследования стало изучение частоты неко-торых аллелей и генотипов гена ФРСЭ среди европеоид-ных пациентов с РА, проживающих в восточных регио-нах России, в сравнении с группой здоровых лиц.…”
unclassified